Effect of Applied Fertilizers and FYM Levels on Productivity of Groundnut (Arachis hypogaea) and their Residual Effect on Succeeding Crop of Isabgol (Plantago ovata Forsk.) - Rathore, M S; Chawra, R S; Singh, I; Chandawat, M S (Annals of Arid Zone, 2016)
Field study aimed to determine nutritional requirement of groundnut to exploit it full production potential and the residual effect of applied nutrients on succeeding crop of blond psyllium to obtain higher return from groundnut and groundnut-blond psyllium cropping sequence was conducted during the year 2007-08 and 2008-09. The study revealed that application of nutrients N: P2O5 20:75 kg ha-1 produced maximum pod yield of groundnut (2830 kg ha-1), net return (Rs. 43,935 ha-1) along with higher B:C ratio of 2.66. The crop responded to 7.5 t FYM ha-1 only. The residual studies reveal that seed yield of blond psyllium enhanced when N: P2O5 applied up to 20:60 kg ha-1 only. However, application of N: P2O5 20:75 kg ha-1 recorded significantly higher groundnut pod equivalent yield (5057 kg ha-1), maximum net return (Rs. 92,214 ha-1) with B:C ratio of 3.70. FYM applied @ 15 t ha-1 gave highest GPEY (4885 kg ha-1), net return (Rs. 87,857 ha-1) along with higher B:C ratio of 3.57.